Vertebral Augmentation can Induce Early Signs of Degeneration in the Adjacent Intervertebral Disc: Evidence from a Rabbit Model. Issue 20 (15th October 2018) - Feng, Zhiyun; Chen, Lunhao; Hu, Xiaojian; Yang, Ge; Chen, Zhong; Wang, Yue
Abstract : Study Design: An experimental study. Objective: The aim of this study was to determine the effect of polymethylmethacrylate (PMMA) augmentation on the adjacent disc. Summary of Background Data: Vertebral augmentation with PMMA reportedly may predispose the adjacent vertebra to fracture. The influence of PMMA augmentation on the adjacent disc, however, remains unclear. Methods: Using a retroperitoneal approach, PMMA augmentation was performed for 23 rabbits. For each animal, at least one vertebra was augmented with 0.2 to 0.3 mL PMMA. The disc adjacent to the augmented vertebra and a proximal control disc were studied using magnetic resonance (MR) imaging, histological and molecular level evaluation at 1, 3, and 6 months postoperatively. Marrow contact channels in the endplate were quantified in histological slices and number of invalid channels (those without erythrocytes inside) was rated. Terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) was performed to determine disc cell apoptosis. Results: On MR images, the signal and height of the adjacent disc did not change 6 months after vertebral augmentation. Histological scores of the adjacent disc increased over time, particularly for the nucleus pulposus. The adjacent disc had greater nucleus degeneration score than the control disc at 3 months (5.7 vs. 4.5, P  < 0.01) and 6 months (6.9 vs. 4.4, P  < 0.001). There were more invalid marrow contact channels in the endplate of augmented vertebra than the control (43.3% vs . 11.1%, P  < 0.01). mRNA of ADAMTS-5, MMP-13, HIF-1α, and caspase-3 were significantly upregulated in the adjacent disc at 3 and 6 months ( P  < 0.05 for all). In addition, there were more TUNEL-positive cells in the adjacent disc than in the control disc (43.4% vs. 24.0%, P  < 0.05) at 6 months postoperatively. Conclusion: Vertebral augmentation can induce early degenerative signs in the adjacent disc, which may be due to impaired nutrient supply to the disc. Level of Evidence: N/A